Vibration Faults Simulation System(VFSS): a lab equipment to aid teaching of Mechatronics Courses - Abdul Muthalif, Asan Gani; Salami, Momoh Jimoh Emiyoka (Tempus Publications, 2004)
VFSS is an example of a mechatronics system which involves data acquisition and analysis using LabVIEW-based virtual instrument technology. This system can serve as teaching equipment for mechatronics students in the area of data acquisition, sensors and actuators, signal processing and vibration monitoring to aid students' understanding on these subjects. Since vibration fault signals and their causes are important for fault detection and diagnosis, a vibration faults simulation system is developed to gain good understanding of such signals. To achieve this a vibration faults simulation rig (VFSR) is designed and developed to simulate and study most common vibration fault signatures encountered in rotating machines. A LabVIEW-based data acquisition system is used to acquire and analyze the fault signals. The complete system has been developed and tested and the fault signals were compared with normal signals so as to ascertain the condition of the machine under investigation. VFSS has been successfully used to demonstrate some vital concepts in the teaching of DSP, sensor and actuators and mechanical vibration since data are acquired from the physical system and are analyzed to derive information on the system under investigation. This approach further allows students to gain insight into effects of noise on measurements and how such effects can be combated.